PENINGKATAN EFISIENSI PROSES PRODUKSIKERAJINAN BAMBU MENGGUNAKAN MESIN PEMBUAT LIDIDI KARTIAJI BAMBOO HANDYCRAFT - V. Lilik Hariyanto, Regina Tutik P., B. Sentot Wijanarka, (Universitas Negeri Yogyakarta, 2013)
The purpose of this devotion is to increase the efficiency of theproduction process of bamboo craft with a round stick making machine.Gains derived by a craftsman can accelerate the process of making bamboohandicraft. Gains derived by devotees is to help solve problems encounteredin the process of manufacture of handicraft artisans.The process of making machines include: planning, manufacture,and testing. The material used is steel square profile 3 cm in size, profilesteel elbow size 3 cm, the steel shaft of 64 mm diameter, Alluminium tomake puley, 15 mm thick wooden board, and 8 mm thick steel plate. Thetools used to make machines include lathes, drilling machines, sawsmachine, and electric welding machines. Machine performance testing doneby measuring the sticks diameter and length are made, and measure the timerequired.The results of the manufacturing process is to have made a roundstick making machine with long dimension of 90 mm, width 50 cm and 65cm high. The machine can make a stick of bamboo with a diameter of 3 mmand 4 mm. Long bamboo stick, not limited or made in accordance with thelength of the cut material. Machine capable of making a round bamboo stickwith a uniform size within 2 minutes to 50 cm long stick.